The Influence of Work Discipline and Motivation Work on Employee Performance (Study in the Field of Infrastructure and Human Resources Development Cililin Regional Hospital, West Bandung Regency) - Fatimah, Siti; Jusdijachlan, R; Avianti, Widiya (International Journal of Psychology and Health Science, 2024)
The purpose of this research is to know and analyze: (1) Work Discipline (2) Work Motivation; (3) performance; and (4) Effect of Work Discipline and Work Motivation on the performance of employees in the Field of Infrastructure and HR Development at Cililin Hospital, West Bandung Regency, either simultaneously or partially. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study were employees of the Infrastructure and HR Development Sector of Cililin Hospital, West Bandung Regency, with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that Work Discipline for employees in the Infrastructure and HR Development Sector of Cililin Hospital, West Bandung Regency, it turned out that employees gave good responses. Work Discipline and Work Motivation simultaneously affect the performance of employees in the Field of Infrastructure and HR Development at Cililin Hospital, West Bandung Regency. But partially Work Discipline dominantly influences employee performance rather than Work Motivation. Because Work Discipline is more dominant in influencing performance, it becomes the first priority in improving employee performance. then employees of the Infrastructure and Human Resources Development Sector of Cililin Hospital in West Bandung Regency are advised to remain consistent with maintaining existing work discipline, so that they are able to work more professionally